Ensuring Equality Before the Law and Personal Data Protection through Implementation of AI Integration in Single Identification Number Systems: A Positivism Philosophy Perspective - Juristo Chiang, Daud; Arifin Hoesin, Zainal (Green Publisher Indonesia, 2024)
The implementation of Artificial Intelligence (AI) in managing single identification number systems, such as Indonesia's National Identity Number, must balance constitutional principles and human rights. AI can enhance administrative efficiency and data security, but it must align with the principle of equality before the law, as stipulated in Articles 27 and 29 of the 1945 Constitution. Ensuring data privacy and preventing discrimination in data processing are essential to avoid regional and social inequality. This study aims to examine how AI-based solutions impact the principles of equality before the law and personal data protection, as well as analyse these issues from the perspective of positivist philosophy, which emphasizes strict legal compliance and effective supervision. Using a normative juridical method with statutory and analytical approaches, this research evaluates existing regulations and explores the interplay between legal structure and AI governance. The findings reveal that while AI can promote efficiency and consistency, its algorithms may also introduce bias, risking unfair outcomes in identification services. A robust regulatory framework and continuous oversight are necessary to address potential inequalities and misuse. From a positivist view, strict rule enforcement and transparent governance are essential to balance technological innovation with the protection of individual rights. [Conclusion] In conclusion, the integration of AI into single identification systems must comply with constitutional and legal principles to uphold equality before the law and protect personal data. Effective legal oversight and accountability are essential to maintain fairness, prevent discrimination, and ensure that AI systems benefit all citizens equitably.